Kualitas Pelayanan Perusahaan Daerah Air Minum (PDAM) Kabupaten Banjarnegara, Purbalingga, Banyumas, dan Cilacap - Hariadi, Pramono; Ramadhanti, Wita (Jurnal Manajemen Akuntansi dan Bisnis, 2008)
Water serves as a crucial need for human beings; no one can survive without water. Due to its importance, in order that people get a fair benefit from it, water management has been undertaken by government via Perusahaan Daerah Air Minum (PDAM). However, PDAM in four regencies (Banyumas, Cilacap, Purbalingga and Banjarnegara) continue to suffer from losses. This study is aimed at (1) finding out the process of services on PDAM in four regencies (Banyumas, Cilacap, Purbalingga and Banjarnegara); (2) measuring the dimension of service quality that have highest effect on PDAM in the above regencies. This study was carried out using survey method and customers of four PDAMs serve as the unit of analysis. The sample size was 200 respondents. Sample was selected through several stages. At the first stage, population was classified by areas. At the second stage, the populations of all regencies were grouped by customer strata. At the third stage, sample of each stratum was proportionately selected by systematic random sampling method. This study found that (1) the services of PDAM in the four regencies are good enough and Banyumas regency is the best services, in other hand Banjarnegara regency is the worst one; (2) tangible has the highest effect to the dimension of service quality. Keywords:Â Â  Perusahaan Daerah Air Minum (PDAM), reliability, responsiveness, assurance, empathy, tangibles